Chitosan electrostatic spinning solution and preparation method thereof

Through homogeneous deacetylation and enzymatic treatment, the molecular weight of chitosan is reduced, combined with a high concentration of acetic acid solution, the problems of complex preparation process of chitosan fiber membranes and poor spinning quality in the prior art are solved, and the preparation of high-quality chitosan electrospinned fiber membranes are achieved.

CN119531010AActive Publication Date: 2025-02-28JIHUA LAB +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411831050.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-28
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing pure chitosan fiber membrane preparation process is complex, and there is a problem of jet instability, resulting in poor spinning quality.

Method used

Chitosan with low deacetylation was prepared by homogeneous deacetylation, and the molecular weight of chitosan was reduced by enzymatic treatment to improve its spinability. A 90% acetic acid solution was used as a solvent to prepare a high concentration of chitosan electrospinning liquid.

Benefits of technology

The preparation process is simplified, the concentration and spinability of pure chitosan nanofibers are improved, and a high-quality chitosan electrospinning fiber membrane is successfully prepared, which is suitable for the repair of difficult wounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119531010A_ABST
    Figure CN119531010A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological materials, and discloses a chitosan electrostatic spinning solution and a preparation method thereof.The preparation method comprises the following steps that chitosan is prepared through a homogeneous deacetylation method; and preparing the chitosan electrostatic spinning solution. The preparation method of the chitosan electrostatic spinning solution is simple and mild, the degree of crystallinity and intermolecular force are reduced by reducing the deacetylation degree and molecular weight of chitosan, the concentration and spinnability of the pure chitosan spinning solution can be improved, and successful preparation of pure chitosan nanofibers is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of biomaterials, and mainly to a chitosan electrospinning solution and a preparation method thereof. Background Art

[0002] Refractory wounds are characterized by high morbidity, difficulty in treatment, and high risk, mainly including traumatic ulcers, diabetic foot, radiation damage, etc., which require intensive and long-term treatment with expensive products, which not only seriously increase the medical burden, but also reduce the quality of life of patients. Therefore, the development of functional dressings for refractory wounds has received extensive research attention. Wound dressings can greatly improve the wound healing microenvironment and are crucial to the healing process. However, existing wound dressings have problems such as single function, poor antibacterial performance and poor wound healing performance.

[0003] In recent years, electrospun nanofiber dressings have attracted extensive attention in the biomedical field due to their unique microstructure and biodegradability. Electrospun nanofibers have high porosity and high specific surface area. Their interconnected three-dimensional porous structure is similar to the natural extracellular matrix. They can not only effectively absorb wound exudate and enhance the penetration of nutrients and oxygen, but also effectively block bacterial infection and promote epidermal cell proliferation and migration. They have broad application prospects in the field of wound dressings.

[0004] Chitosan is a product of chitin deacetylation. It has excellent biocompatibility and biodegradability. It also has biological activities such as antibacterial, antioxidant, hemostatic, and wound healing. It is widely used in the field of medical dressings. Due to the large number of hydrogen bond interactions within and between molecules, chitosan is difficult to dissolve alone in conventional solvents. It is often dissolved in dilute acid solutions such as acetic acid, trifluoroacetic acid, hydrochloric acid or phosphoric acid. However, chitosan has low solubility and high solution viscosity, and its polycationic properties repel each other under the action of electric field force. There will be problems of jet instability during electrospinning, which greatly limits its preparation process. Reports on chitosan electrospinning mainly focus on blending with other flexible water-soluble polymers, such as polyethylene oxide, polyvinyl alcohol or polyvinyl pyrrolidone (CN 113445155 A). CN110295401 A proposes to use ionic liquid in 1-ethyl-3-methylimidazolium acetate as solvent, and adjust the viscosity of spinning solution by organic solvent N,N'-dimethylformamide (or N,N'-dimethylacetamide) to prepare pure chitosan ultrafine fiber. However, ionic liquid is expensive and the preparation process is complicated. CN 117535825 A proposes to add dilute alkali aqueous solution to chitosan dilute acid solution to form hydrogel, reduce the crystallinity and hydrogen bond interaction of chitosan, and then dissolve in hexafluoroisopropanol after sufficient water washing for electrostatic spinning. This scheme has high process requirements and complicated process.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a chitosan electrospinning solution and a preparation method thereof, aiming to solve the problem of complex preparation process of existing pure chitosan fiber membranes.

[0007] The technical solution of this application is as follows: A method for preparing a chitosan electrospinning solution, comprising the following steps: Chitosan was prepared by homogeneous deacetylation method: chitosan powder was evenly dispersed in sodium hydroxide crushed ice, stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasonication, and then frozen at -15°C to -30°C for 12 to 48 hours, and then taken out and thawed naturally; the chitosan solution was obtained by heating and stirring in a 25 to 60°C water bath for a homogeneous deacetylation reaction, and the reaction time was 6 to 48 hours to obtain a deacetylated chitosan solution; the deacetylated chitosan solution was poured into anhydrous ethanol for precipitation, and washed with an ethanol solution with a volume concentration of 80% until neutral, and freeze-dried to obtain the chitosan with a deacetylation degree of 20 to 70%; Preparation of the chitosan electrospinning solution: dissolving the chitosan in an acetic acid solution with a mass concentration of 90%, wherein the mass concentration of the chitosan in the acetic acid solution is 2-12 wt%, to obtain the chitosan electrospinning solution.

[0008] The preparation method of the chitosan electrospinning solution of the present application is simple and mild, and can improve the concentration and spinnability of the pure chitosan spinning solution, which is conducive to the successful preparation of pure chitosan nanofibers.

[0009] The method for preparing the chitosan electrospinning solution, wherein the amount of the chitosan powder added is 3-6 g of the chitosan powder per 600 mL of the sodium hydroxide crushed ice; The mass concentration of sodium hydroxide in the sodium hydroxide crushed ice is 5-40 wt %.

[0010] In this application, the step of dissolving chitosan powder is optimized, the sodium hydroxide solution is frozen into sodium hydroxide crushed ice and then crushed into crushed ice, and the chitosan powder is directly dispersed in the sodium hydroxide crushed ice, so that the temperature of the entire reaction system can be uniform, and the chitosan is uniformly dissolved. The above ratio can ensure that the chitosan can be completely dissolved after the NaOH crushed ice and the subsequent freeze-thaw cycle. If the amount of chitosan added is too much, the number of subsequent freeze-thaw cycles needs to be increased, which takes more time.

[0011] In the method for preparing the chitosan electrospinning solution, the amount of the anhydrous ethanol used is 4 times the volume of the deacetylated chitosan solution.

[0012] The method for preparing chitosan electrospinning solution, wherein, in the process of ultrasonically removing bubbles, the ultrasonic power is 500W and the ultrasonic time is 5 min.

[0013] The method for preparing the chitosan electrospinning solution, wherein the method for preparing the chitosan electrospinning solution further comprises the following steps before the step of preparing the chitosan electrospinning solution: The chitosan is subjected to enzymatic hydrolysis so that the molecular weight range of the chitosan is 200-700 kDa.

[0014] The method for preparing chitosan electrospinning solution, wherein the step of enzymatically hydrolyzing the chitosan specifically comprises the following steps: The chitosan is dissolved in an acetic acid solution with a mass concentration of 1-2%, chitosanase is added, and the mixture is stirred in a water bath at 25-60° C. for enzymolysis for 0.5-4 h.

[0015] The method for preparing the chitosan electrospinning solution comprises dissolving 0.5-2 g of the chitosan in 100 mL of the acetic acid solution having a mass concentration of 1-2%.

[0016] The method for preparing the chitosan electrospinning solution comprises adding 2 to 10 mg of the chitosan enzyme to every 1 g of the chitosan.

[0017] The method for preparing the chitosan electrospinning solution, wherein, in the step of preparing the chitosan electrospinning solution, when the molecular weight of the chitosan is 690 kDa, the mass concentration of the chitosan in the acetic acid solution is 4-5 wt%, and when the molecular weight of the chitosan is 340 kDa, the mass concentration of the chitosan in the acetic acid solution is 9-11 wt%.

[0018] A chitosan electrostatic spinning solution is prepared by the above-mentioned preparation method of the chitosan electrostatic spinning solution.

[0019] Beneficial effects: The preparation method of the chitosan electrospinning solution of the present application is simple and mild. By reducing the degree of deacetylation and molecular weight of chitosan, the crystallinity and intermolecular forces are reduced, the concentration and spinnability of the pure chitosan spinning solution can be improved, which is conducive to the successful preparation of pure chitosan nanofibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope image of the chitosan electrospun fiber membrane prepared in Example 1 of the present application.

[0021] Figure 2 This is a scanning electron microscope image of the chitosan electrospun fiber membrane prepared in Example 2 of the present application.

[0022] Figure 3 This is a scanning electron microscope image of the chitosan electrospun fiber membrane prepared in Example 3 of the present application.

[0023] Figure 4 This is a scanning electron microscope image of the chitosan electrospun fiber membrane prepared in Example 4 of the present application.

[0024] Figure 5 The figure is a diagram of the cytotoxicity test results of Examples 1-4. DETAILED DESCRIPTION

[0025] The present application provides a chitosan electrospinning solution and a preparation method thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0026] The present application is to provide a method for preparing a pure chitosan electrospinning solution that is simple, does not require the addition of any spinning aids, and can be applied to the repair of refractory wounds. Low deacetylation chitosan is used as a raw material to reduce the number of protonated amino groups in the acid solution system, thereby reducing the influence of intermolecular electrostatic repulsion on the spinning process. For chitosan with a deacetylation degree of about 50% prepared by a homogeneous deacetylation process, since the N-acetyl groups are randomly distributed and the deviation is minimal, the secondary structure of the chitosan molecule can be destroyed to the greatest extent, the crystallinity and intermolecular forces can be weakened, and the spinnability can be enhanced. In addition, by reducing the molecular weight of chitosan, its intermolecular forces can be further reduced, while reducing the viscosity of the spinning solution and increasing the concentration of the spinning solution.

[0027] Chitosan has excellent biocompatibility and biodegradability, and also has biological activities such as antibacterial, anti-inflammatory, hemostatic and wound healing. The chitosan nanofiber membrane constructed by electrospinning technology not only retains the above excellent biological activities, but also has a structure similar to the extracellular matrix, which can promote the proliferation and migration of epidermal cells. The antibacterial properties of chitosan itself and the physical barrier effect provided by the nanofiber membrane can provide double protection for the wound surface, while ensuring the breathability of the wound dressing. In addition, chitosan with a deacetylation degree of about 50% greatly increases the hydrophilicity of the nanofiber due to its low crystallinity and interchain hydrogen bonds, which is more conducive to the absorption of wound exudate and accelerates the migration of epidermal cells. It is an ideal wound dressing material.

[0028] Specifically, the preparation method of the chitosan electrospinning solution of the present application comprises the following steps: (1) Chitosan is prepared by homogeneous deacetylation method: The chitosan powder was evenly dispersed in sodium hydroxide crushed ice (NaOH mass concentration was 5-40 wt%), stirred until the sodium hydroxide crushed ice was completely melted, and after removing bubbles by ultrasonic, it was frozen at -15℃~-30℃ for 12-48 h, and then taken out and thawed naturally; The chitosan solution was obtained by heating and stirring in a water bath at 25-60°C for homogeneous deacetylation for 6-48 hours. The deacetylated chitosan solution was poured into 4 times the volume of anhydrous ethanol for precipitation, washed with an ethanol solution with a volume concentration of 80% until neutral, and freeze-dried to obtain chitosan with a deacetylation degree of 20-70%.

[0029] In step (1), the amount of chitosan powder added can be 3-6 g of chitosan powder per 600 mL of sodium hydroxide crushed ice. Through multiple experiments, it has been verified that the above ratio can ensure that chitosan can be completely dissolved after NaOH crushed ice and a subsequent freeze-thaw cycle. If too much chitosan is added, the number of subsequent freeze-thaw cycles needs to be increased, which takes more time.

[0030] Moreover, in the prior art, chitosan powder and sodium hydroxide solution are generally mixed in an ice bath, but this method is not suitable for large-scale production. If the amount of solution used for production is large, there will be a temperature difference between the edge and the center of the container when chitosan powder and sodium hydroxide solution are mixed in an ice bath, and the center temperature is difficult to reach about 0°C, which will cause uneven dissolution of chitosan. Therefore, the step of dissolving chitosan powder is optimized in this application, and the sodium hydroxide solution is frozen into sodium hydroxide crushed ice and then crushed into crushed ice, and the chitosan powder is directly dispersed in the sodium hydroxide crushed ice, so that the temperature of the entire reaction system can be uniform, ensuring uniform dissolution of chitosan.

[0031] In step (1), the step of freezing at -15℃~-30℃ for 12~48h is to allow water molecules and NaOH molecules to form ice crystals. The mechanical force generated by the formation and growth of ice crystals can destroy the dense crystal structure inside chitin, thereby dissolving chitin. The temperature required for freezing is -15℃~-30℃. In this temperature range, the formation and growth of ice crystals are slow, the ice crystals are larger, and can destroy the crystal structure to a greater extent; but when the temperature is lower than -30℃, the ice crystal formation process is fast and the ice crystals are small, which is not enough to destroy the crystal structure of chitin, so the solubility is poor.

[0032] In step (1), a homogeneous deacetylation reaction is carried out by heating and stirring in a water bath at 25-60°C. The reaction time is 6-48 hours. The degree of deacetylation is controlled by controlling different reaction times. Generally speaking, a reaction time of 8 hours corresponds to a deacetylation degree of 28%, a reaction time of 16 hours corresponds to a deacetylation degree of 51%, and a reaction time of 24 hours corresponds to a deacetylation degree of 63%.

[0033] In step (1), the deacetylated chitosan is poured into 4 times the volume of anhydrous ethanol for precipitation. Using 4 times the volume of anhydrous ethanol is the minimum amount that can completely precipitate the chitosan. Further increasing the ethanol content will not increase the yield. However, it is not recommended to reduce the amount of anhydrous ethanol because it will reduce the yield.

[0034] In step (1), during the process of ultrasonically removing bubbles, the ultrasonic power can be 500 W and the ultrasonic time can be 5 min.

[0035] (2) Enzymatic hydrolysis of chitosan: The chitosan prepared in step (1) is dissolved in an acetic acid solution having a mass concentration of 1-2%, and then chitosanase is added, and the mixture is stirred in a water bath at 25-60° C. for enzymolysis for 0.5-4 h to obtain chitosan with a molecular weight range (weight average molecular weight) of 200-700 kDa.

[0036] In step (2), by optimizing the concentration of chitosan in the acetic acid solution and the amount of chitosanase added, the viscosity and reaction rate of the reaction system are adjusted to a moderate level, thereby making the molecular weight highly controllable.

[0037] Specifically, every 0.5-2 g of chitosan can be dissolved in 100 mL of acetic acid solution with a mass concentration of 1-2%. The advantage of using the above ratio is that the viscosity of the chitosan after dissolution is moderate, and it can be easily stirred in the early stage of enzyme degradation, which is conducive to ensuring the uniformity of the reaction system. If the viscosity is too high, it will be difficult to stir, which will make the reaction system prone to unevenness, resulting in a wider molecular weight distribution of chitosan.

[0038] Specifically, 2-10 mg chitosanase can be added to every 1g chitosan. The amount of chitosanase added is based on the reaction speed. This addition ratio can make the reaction milder and obtain parameters of different molecular weights in a short time. If the amount added is small, the degradation rate is slow, which will greatly extend the reaction time. If the amount added is too much, the degradation rate will be too fast, the uniformity of the reaction will be reduced, the reaction time will be short, and it will be difficult to collect chitosan of different molecular weights.

[0039] In step (2), during the process of stirring the enzymatic hydrolysis in a water bath at 25-60°C for 0.5-4h, if the temperature is too low, the reaction rate will slow down, and if the temperature is increased, the reaction rate will be accelerated. However, the chitosan raw material itself is prone to browning when heated for a long time, so it is not recommended to exceed 60°C. In the present application scheme, the molecular weight of the prepared chitosan is mainly controlled by controlling the enzymatic hydrolysis time. The longer the reaction time, the lower the molecular weight.

[0040] (3) Preparation of chitosan electrospinning solution: Chitosan was dissolved in an acetic acid solution with a mass concentration of 90%, and the mass concentration of chitosan in the acetic acid solution was 2-12 wt%, to obtain a chitosan electrospinning solution.

[0041] For chitosan raw materials with the above molecular weight range and deacetylation degree range, the mass concentration of chitosan in the chitosan electrospinning solution is 2~12 wt%, which can ensure that the chitosan electrospinning solution has spinnability. Chitosans of different molecular weights correspond to different optimal concentrations, and the smaller the molecular weight, the higher the optimal concentration. For example, for chitosan raw materials with a molecular weight of 690 kDa, the preferred concentration is 4~5 wt%, and for chitosan raw materials with a molecular weight of 340 kDa, the preferred concentration is 9~11 wt%.

[0042] In the present application, the chitosan prepared in step (1) can also be directly used to prepare chitosan electrospinning solution without enzymatic hydrolysis in step (2). The chitosan electrospinning solution that has not been enzymatically hydrolyzed can also be used for electrospinning. However, due to the large molecular weight of chitosan, the concentration of chitosan electrospinning solution is low but the viscosity is high, the critical voltage required for spinning is large, and droplets are prone to occur during the spinning process, resulting in poor nanofiber morphology. Therefore, in the present application, it is preferred to further reduce the molecular weight of chitosan by enzymatic hydrolysis, which can increase the concentration of chitosan electrospinning solution and reduce the viscosity of chitosan electrospinning solution, which is beneficial to increase the entanglement of solution molecular chains during spinning, improve spinnability, make the nanofiber morphology uniform, and improve spinning efficiency. However, the molecular weight of chitosan cannot be too low, otherwise the polymer jet will break during the spinning process, resulting in point spraying.

[0043] The preparation method of chitosan electrospinning solution of the present application has the following advantages: (1) The present application reduces the crystallinity and intermolecular interaction of chitosan by reducing the deacetylation degree and molecular weight of chitosan, thereby improving the spinnability of pure chitosan without adding any additives; (2) The spinning solution prepared by the above preparation method can be used to prepare a fiber membrane through a simple and mild process, which is beneficial to ensure the biological activity of the fiber membrane and makes the prepared fiber membrane a potential wound repair material.

[0044] The present application also provides a chitosan electrospinning solution, which is prepared by the above-mentioned preparation method of the chitosan electrospinning solution.

[0045] The chitosan electrospinning solution of the present application can be used for electrospinning, and a chitosan electrospinning fiber membrane can be prepared by electrospinning.

[0046] The chitosan electrospinning solution of the present application can be spun using conventional electrospinning technology.

[0047] In the present application, a method for preparing a chitosan electrospinning fiber membrane is also provided, comprising the following steps: (1) Preparation of electrospinning fiber membrane: The chitosan electrospinning solution was used as the spinning solution to prepare the electrospinning fiber membrane. The spinning parameters were set as follows: positive electrode voltage was 15-20 kV, negative electrode voltage was -3 kV, spinning solution flow rate was 0.2-3 mL / h, receiving distance was 10-25 cm, and air humidity was 30-60%.

[0048] In step (1), the air humidity is preferably 30%. The electrospun fiber membrane produced under this air humidity has a better fiber morphology.

[0049] (2) Post-treatment of electrospun fiber membrane: Preparation of solidifying liquid: Sodium hydroxide is dissolved in an ethanol aqueous solution with a volume concentration of 75% to prepare a solidifying liquid, and the mass concentration of sodium hydroxide in the ethanol aqueous solution is 5wt%.

[0050] The electrospun fiber membrane was immersed in a mixture of ethanol and sodium hydroxide for at least 4 h, then washed with water until neutral, and dried at room temperature to obtain a chitosan electrospun fiber membrane.

[0051] In step (2), the water-soluble electrospun fiber membrane is solidified by soaking in a mixture of ethanol and sodium hydroxide for at least 4 h, stabilizing its nanofiber structure and making it insoluble in water. This solidification method should also be applicable to fiber membranes of other chitosan systems.

[0052] In the present application, a pure chitosan electrospinning fiber membrane is also provided, which is prepared by the preparation method of the above-mentioned chitosan electrospinning fiber membrane. In the present application, pure chitosan refers to a membrane that does not contain other flexible water-soluble polymers. However, in the preparation method of the above-mentioned chitosan electrospinning solution, chitosanase is basically removed during the chitosan raw material sedimentation and washing process, and acetic acid is also removed in the electrospinning membrane post-treatment in the preparation method of the above-mentioned chitosan electrospinning fiber membrane. Therefore, the pure chitosan electrospinning fiber membrane of the present application, in addition to not containing other flexible water-soluble polymers, also basically does not contain chitosanase and acetic acid, so that the prepared pure chitosan electrospinning fiber membrane can better exert the biological activity of chitosan.

[0053] The present application is further described below through specific embodiments.

[0054] Embodiment 1: (1) Preparation of spinning solution: 4.5 g chitosan powder was evenly dispersed in 600 mL sodium hydroxide crushed ice (NaOH mass concentration was 15 wt%), stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasound (ultrasonic power was 500 W, ultrasonic time was 5 min), and then frozen at -20℃ for 24 h, and taken out to thaw naturally. Then, the homogeneous deacetylation reaction was carried out by heating and stirring in a 40℃ water bath for 16 h. Then, the deacetylated chitosan solution was poured into 4 times the volume of anhydrous ethanol for precipitation, washed with 80% ethanol solution to neutrality, and freeze-dried to obtain chitosan with a deacetylation degree of 51%. After testing, the weight average molecular weight of undegraded chitosan was 690 kDa. The above chitosan was dissolved in 90% acetic acid solution with a mass concentration of 4.5 wt%.

[0055] (2) Preparation of chitosan electrospun fiber membrane: Chitosan electrospun fiber membrane was prepared by electrospinning. The spinning conditions were as follows: positive electrode voltage of 18 kV, negative electrode voltage of -3 kV, spinning solution flow rate of 0.8 ml / h, receiving distance of 20 cm, and air humidity of 50%.

[0056] (3) Post-treatment of electrospun fiber membrane: Sodium hydroxide was dissolved in an ethanol aqueous solution with a volume concentration of 75% to prepare a curing solution, and the mass concentration of sodium hydroxide in the ethanol aqueous solution was 5wt%. The electrospun fiber membrane was immersed in the curing solution for 4 h, then washed with water until neutral, and dried at room temperature to obtain a chitosan electrospun fiber membrane.

[0057] Example 2: (The main difference from Example 1 is the different degree of deacetylation) (1) Preparation of spinning solution: 4.5 g chitosan powder was evenly dispersed in 600 mL sodium hydroxide crushed ice (NaOH mass concentration was 15 wt%), stirred until the sodium hydroxide crushed ice was completely melted, and the bubbles were removed by ultrasound (ultrasonic power was 500 W, ultrasonic time was 5 min), and then frozen at -20℃ for 24 h, and then taken out and thawed naturally. Then, the homogeneous deacetylation reaction was carried out by heating and stirring in a 40℃ water bath for 24 h. The deacetylated chitosan solution was then poured into 4 times the volume of anhydrous ethanol for precipitation, washed with 80% ethanol solution to neutrality, and freeze-dried to obtain chitosan with a deacetylation degree of 63%. After testing, the weight average molecular weight of undegraded chitosan was 690 kDa. The above chitosan was dissolved in 90% acetic acid solution with a mass concentration of 4.5 wt%.

[0058] (2) Preparation of chitosan electrospun fiber membrane: Chitosan electrospun fiber membrane was prepared by electrospinning. The spinning conditions were as follows: positive electrode voltage of 18 kV, negative electrode voltage of -3 kV, spinning solution flow rate of 0.8 ml / h, receiving distance of 20 cm, and air humidity of 50%.

[0059] (3) Post-treatment of electrospun fiber membrane: Sodium hydroxide was dissolved in an ethanol aqueous solution with a volume concentration of 75% to prepare a curing solution, and the mass concentration of sodium hydroxide in the ethanol aqueous solution was 5wt%. The electrospun fiber membrane was immersed in the curing solution for 4 h, then washed with water until neutral, and dried at room temperature to obtain a chitosan electrospun fiber membrane.

[0060] Example 3: (The main difference from Example 1 is the different molecular weight) (1) Preparation of spinning solution: 4.5 g chitosan powder was evenly dispersed in 600 mL sodium hydroxide crushed ice (NaOH mass concentration was 15 wt%), stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasound (ultrasonic power was 500 W, ultrasonic time was 5 min), and then frozen at -20℃ for 24 h, and taken out to thaw naturally. Then, the homogeneous deacetylation reaction was carried out by heating and stirring in a 40℃ water bath for 16 h. Then, the deacetylated chitosan solution was poured into 4 times the volume of anhydrous ethanol for precipitation, washed with 80% ethanol solution to neutrality, and freeze-dried to obtain chitosan with a deacetylation degree of 51%. 1 g chitosan was dissolved in 100 mL 1% acetic acid solution, and then 5 mg chitosanase was added. The chitosan was hydrolyzed by stirring in a 40℃ water bath for 1.5 h. The weight average molecular weight of chitosan was 340 kDa. The chitosan was dissolved in an acetic acid solution having a mass concentration of 90% to a mass concentration of 10 wt%.

[0061] (2) Preparation of chitosan electrospun fiber membrane: Chitosan electrospun fiber membrane was prepared by electrospinning. The spinning conditions were as follows: positive electrode voltage of 18 kV, negative electrode voltage of -3 kV, spinning solution flow rate of 0.8 ml / h, receiving distance of 20 cm, and air humidity of 50%.

[0062] (3) Post-treatment of electrospun fiber membrane: Sodium hydroxide was dissolved in an ethanol aqueous solution with a volume concentration of 75% to prepare a curing solution, and the mass concentration of sodium hydroxide in the ethanol aqueous solution was 5wt%. The electrospun fiber membrane was immersed in the curing solution for 4 h, then washed with water until neutral, and dried at room temperature to obtain a chitosan electrospun fiber membrane.

[0063] Example 4: (The main difference from Example 3 is the difference in air humidity) (1) Preparation of spinning solution: 4.5 g chitosan powder was evenly dispersed in 600 mL sodium hydroxide crushed ice (NaOH mass concentration was 15 wt%), stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasound (ultrasonic power was 500 W, ultrasonic time was 5 min), and then frozen at -20℃ for 24 h, and taken out to thaw naturally. Then, the homogeneous deacetylation reaction was carried out by heating and stirring in a 40℃ water bath for 16 h. Then, the deacetylated chitosan solution was poured into 4 times the volume of anhydrous ethanol for precipitation, washed with 80% ethanol solution to neutrality, and freeze-dried to obtain chitosan with a deacetylation degree of 51%. 1 g chitosan was dissolved in 100 mL 1% acetic acid solution, and then 5 mg chitosanase was added. The chitosan was hydrolyzed by stirring in a 40℃ water bath for 1.5 h. The weight average molecular weight of chitosan was 340 kDa. The chitosan was dissolved in an acetic acid solution having a mass concentration of 90% to a mass concentration of 10 wt%.

[0064] (2) Preparation of chitosan electrospun fiber membrane: Chitosan electrospun fiber membrane was prepared by electrospinning. The spinning conditions were as follows: positive electrode voltage of 18 kV, negative electrode voltage of -3 kV, spinning solution flow rate of 0.8 ml / h, receiving distance of 20 cm, and air humidity of 30%.

[0065] (3) Post-treatment of electrospun fiber membrane: Sodium hydroxide was dissolved in an ethanol aqueous solution with a volume concentration of 75% to prepare a curing solution, and the mass concentration of sodium hydroxide in the ethanol aqueous solution was 5wt%. The electrospun fiber membrane was immersed in the curing solution for 4 h, then washed with water until neutral, and dried at room temperature to obtain a chitosan electrospun fiber membrane.

[0066] Figure 1-3 These are scanning electron microscope images of the chitosan electrospun fiber membranes prepared in Examples 1-3, respectively. Figure 1-3It shows that the prepared spinning solution is spinnable, but the concentration of the spinning solution in Example 1 and Example 2 is low, so some bead structures will appear, while Example 3 increases the concentration of the spinning solution while reducing the molecular weight, making the nanofiber structure more uniform. The difference between Example 3 and Example 1 is that there is an additional enzymatic hydrolysis step. It can be seen from Example 1 and Example 3 that the spinning solution without enzymatic hydrolysis can also be spun, but droplets will appear during the spinning process of Example 1, resulting in poor nanofiber morphology. In Example 3, the molecular weight of chitosan is reduced by enzymatic hydrolysis, the concentration of the spinning solution is increased, and the prepared nanofiber morphology is uniform.

[0067] Figure 4 The scanning electron microscope image of the chitosan electrospun fiber membrane prepared in Example 4. Example 4 was prepared under relatively low air humidity conditions. Figure 4 It can be seen that there is a clear nanofiber structure without beading, indicating good spinning performance.

[0068] Figure 5 Graph showing the cytotoxicity test results of Examples 1-4. The cell activity of each group was >80%, indicating that the chitosan electrospun fiber membranes prepared in Examples 1-4 had excellent biocompatibility. Among them, the method for the above-mentioned cytotoxicity test is to test the cytotoxicity of the chitosan electrospun fiber membrane prepared in Examples 1-4 by a direct contact method: L929 cells are cultured in a culture medium (DMEM) supplemented with 10% fetal bovine serum and 1% penicillin-streptomycin solution; chitosan electrospun fiber membranes prepared in Examples 1-4 with a diameter of 1 cm are added to 24-well plates respectively, and then L929 cells are inoculated on the surface of the chitosan electrospun fiber membrane at a density of 80,000 cells per well, and the 24-well plate is placed in a humidified atmosphere of 37°C and 5% CO2 for culture, and the control group is a standard culture medium; after culturing for 24 hours, a culture medium supplemented with 10% CCK-8 reagent is added to each well, and then cultured for another 2 hours, and the absorbance of each well at 450 nm is recorded using a microplate reader (Bio-Tek ELx800, USA).

[0069] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.

Claims

1. A method for preparing a chitosan electrospinning solution, characterized in that: The following steps are involved: Chitosan was prepared by homogeneous deacetylation method: chitosan powder was evenly dispersed in sodium hydroxide crushed ice, stirred until the sodium hydroxide crushed ice was completely melted, and bubbles were removed by ultrasonication, and then frozen at -15°C to -30°C for 12 to 48 hours, and then taken out and thawed naturally; the chitosan solution was obtained by heating and stirring in a 25 to 60°C water bath for a homogeneous deacetylation reaction, and the reaction time was 6 to 48 hours to obtain a deacetylated chitosan solution; the deacetylated chitosan solution was poured into anhydrous ethanol for precipitation, and washed with an ethanol solution with a volume concentration of 80% until neutral, and freeze-dried to obtain the chitosan with a deacetylation degree of 20 to 70%; Preparation of the chitosan electrospinning solution: dissolving the chitosan in an acetic acid solution with a mass concentration of 90%, wherein the mass concentration of the chitosan in the acetic acid solution is 2-12 wt%, to obtain the chitosan electrospinning solution.

2. The method for preparing chitosan electrospinning solution according to claim 1, characterized in that: The chitosan powder is added in an amount of 3 to 6 g per 600 mL of sodium hydroxide crushed ice; The mass concentration of sodium hydroxide in the sodium hydroxide crushed ice is 5-40 wt %.

3. The method for preparing chitosan electrospinning solution according to claim 1, characterized in that: The amount of the anhydrous ethanol used is 4 times the volume of the deacetylated chitosan solution.

4. The method for preparing chitosan electrospinning solution according to claim 1, characterized in that: In the process of ultrasonically removing bubbles, the ultrasonic power is 500W and the ultrasonic time is 5 min.

5. The method for preparing chitosan electrospinning solution according to claim 1, characterized in that: The method for preparing the chitosan electrospinning solution further comprises the following steps before the step of preparing the chitosan electrospinning solution: The chitosan is subjected to enzymatic hydrolysis so that the molecular weight range of the chitosan is 200-700 kDa.

6. The method for preparing chitosan electrospinning solution according to claim 5, characterized in that: The step of enzymatically treating the chitosan specifically comprises the following steps: The chitosan is dissolved in an acetic acid solution with a mass concentration of 1-2%, chitosanase is added, and the mixture is stirred in a water bath at 25-60° C. for enzymolysis for 0.5-4 h.

7. The method for preparing chitosan electrospinning solution according to claim 6, characterized in that: Every 0.5-2 g of the chitosan is dissolved in 100 mL of the acetic acid solution having a mass concentration of 1-2%.

8. The method for preparing chitosan electrospinning solution according to claim 6, characterized in that: 2-10 mg of the chitosanase is added per 1 g of the chitosan.

9. The method for preparing chitosan electrospinning solution according to claim 5, characterized in that: In the step of preparing the chitosan electrospinning solution, when the molecular weight of the chitosan is 690 kDa, the mass concentration of the chitosan in the acetic acid solution is 4-5 wt%, and when the molecular weight of the chitosan is 340 kDa, the mass concentration of the chitosan in the acetic acid solution is 9-11 wt%.

10. A chitosan electrospinning solution, characterized in that: The chitosan electrospinning solution is prepared by the method for preparing the chitosan electrospinning solution as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of pure-chitosan superfine fibers

    CN110295401A

  • Chitosan-based nanofiber and preparation method thereof

    CN113445155A

  • Preparation method of pure chitosan nanofiber

    CN117535825A

  • Method for preparing a series of chitosan oligosaccharides in different degrees of deacetylation and polymerization by means of microwave process reinforcement

    CN109400948A

  • Chitosan-based composition with weight-losing and lipid-lowering functions as well as preparation method and application of chitosan-based composition

    CN112972489A